Pengaruh Pola Komunikasi Orang Tua terhadap Anak Pelaku Tawuran di Wilayah Rawabunga - Sahra Adisti; Mareta Puri Rahastine (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
Abstract this study aims to determine the influence of parental communication patterns on adolescents involvement in gang fights in the Rawabunga area, East Jakarta. Adolescents involved in such conflicts often experience communication barriers wuthin their families, mainly due to authoritatian, permissive, or closed communication styyles. This research employee a quantitative associative approach with Purposive Sampling technique. A total of 65 adolescents responden tsb with a history of involvement in gang fights were selected. Data were collected using a Linkert scale questionnaire and analyzed through validity test, reability tests, simple linear regression, and t-tests using SPSS. The results showed a significant negative influence between parental communication patterns and adilescents’ involvement in gang fights. The better the communication between parents and children, the lower the tendency of adolescents to engage in such behavior. The findings emphasize the importance of open, empathetic, and sipportive communication in families to prevent deviant behavior among adolescents.